Effects of transcranial direct current stimulation on the rehabilitation of painful shoulder following a stroke: protocol for a randomized, controlled, double-blind, clinical trial - de Souza, Janaina Andressa (Trials, 2019)
BACKGROUND: Shoulder pain is reported to be one of the major challenges faced in the functional recovery of patients in rehabilitation following a stroke. In such cases, transcranial direct current stimulation (tDCS) has been used as an additional therapeutic tool for improvements in central and peripheral pain. The aim of the proposed study is to evaluate the effect of tDCS when combined with upper limb physical therapy on pain intensity and functional improvement in stroke survivors with shoulder pain in the hemiplegic limb. METHODS: A randomized, placebo-controlled, double-blind, clinical trial is proposed. The volunteers will be randomly allocated to receive passive movement on the upper limb, which will be performed by the therapist for 20 min followed by either active tDCS or sham tDCS (current stimulation for 30 s) during simultaneous physical activity of the upper limb (“mini-bike”) for 20 min, totaling 40 min of intervention performed in 10 consecutive sessions. The anode electrode will be positioned over the primary motor cortex with a current of 2 mA and the cathode electrode will be positioned in the supraorbital region contralateral to the anode. The primary outcome will be shoulder pain intensity, which will be measured using the visual analog scale (VAS) on three occasions: 1) pre-intervention; 2) after 10 interventions (5 weekly sessions, for 2 weeks); and 3) 30 days after the end of the interventions. The secondary outcomes will be motor performance, upper limb function, and quality of life. TRIAL REGISTRATION: Brazilian Registry of Clinical Trials, RBR-8F5MNY. Registered on June 2, 2017. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13063-019-3266-y) contains supplementary material, which is available to authorized users.